2013
DOI: 10.1002/oby.20541
|View full text |Cite
|
Sign up to set email alerts
|

Obesity rather than regional fat depots marks the metabolomic pattern of adipose tissue: An untargeted metabolomic approach

Abstract: Objective: This study compares the patterns of visceral (VIS) and subcutaneous (SC) adipose tissue (AT)-derived metabolites from non-obese (BMI 24-26 kg/m2) and obese subjects (BMI > 40 kg/m2) with no major metabolic risk factors other than BMI. Methods: SC-and VIS-AT obtained from obese (Ob) and non-obese (NOb) subjects during surgery were incubated to obtain their metabolites. Differences related to obesity or anatomical provenances of AT were assessed using an untargeted metabolomics approach based on gas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…More recently, it has been shown that obesity blunts amino acid metabolism in adipose tissue and profoundly affects BCAA catabolism. In subcutaneous and visceral adipose tissue obtained during surgery, essential amino acids, leucine, glutamine and serine and 2-ketoisocaproic acid differed significantly between obese and lean subjects [41]. In our earlier study of MZ twin pairs discordant for obesity, serum levels of insulin secretionenhancing BCAA were increased in obese male co-twins and adipose tissue transcription profiles exposed significant down-regulation of genes involved with mitochondrial BCAA catabolism [3,42] indicating that the increase in plasma BCAA levels may be due to their decreased oxidation in the peripheral tissues.…”
Section: Discussionmentioning
confidence: 91%
“…More recently, it has been shown that obesity blunts amino acid metabolism in adipose tissue and profoundly affects BCAA catabolism. In subcutaneous and visceral adipose tissue obtained during surgery, essential amino acids, leucine, glutamine and serine and 2-ketoisocaproic acid differed significantly between obese and lean subjects [41]. In our earlier study of MZ twin pairs discordant for obesity, serum levels of insulin secretionenhancing BCAA were increased in obese male co-twins and adipose tissue transcription profiles exposed significant down-regulation of genes involved with mitochondrial BCAA catabolism [3,42] indicating that the increase in plasma BCAA levels may be due to their decreased oxidation in the peripheral tissues.…”
Section: Discussionmentioning
confidence: 91%
“…Metabolomics based on gas chromatography techniques has been previously tested in adipose tissue from differential locations [9]. Although it is robust, this technique shows a relatively low number of potential candidates when compared with liquid chromatography coupled with high-precision mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have focused on plasma metabolite alterations in obesity, insulin resistance, and type 2 diabetes, only a few studies have considered body fat distribution, other markers of cardiometabolic risk (13,44,55), and possible depot-specific alterations in BCAA-catabolizing enzymes (15,19). In addition, only one study has performed metabolomicsbased AA analysis including human visceral and subcutaneous adipose tissue from nonobese and obese individuals (13).…”
mentioning
confidence: 99%
“…In addition, only one study has performed metabolomicsbased AA analysis including human visceral and subcutaneous adipose tissue from nonobese and obese individuals (13). Thus, we attempted to identify which features of the plasma metabolite signature of obesity were related to visceral obesity and cardiometabolic risk factors and assessed possible depot-specific alterations in expression and protein levels of BCAAcatabolizing enzymes in visceral and subcutaneous adipose tissue.…”
mentioning
confidence: 99%